PERAN SISTEM INFORMASI AKUNTANSI (SIA) TERHADAP KEUANGAN - Wahyu Widjayanti; Windy Dwiparaswati; Ivan Maurits (Jurnal Teknik dan Science, 2024)
The Accounting Information System (AIS) plays a crucial role in optimizing financial processes across various types of organizations. AIS implementation enables real-time integration of financial data, improves the accuracy of financial reporting, and facilitates better strategic decision-making. This study aims to evaluate the effectiveness of AIS in enhancing operational efficiency and financial reporting accuracy. The study employs a case analysis method on organizations that have implemented AIS. The results indicate that AIS significantly contributes to improving financial management efficiency, accelerating report processing time, and strengthening internal controls. Thus, AIS proves to be an effective tool for transparent and accountable financial management.